Monitoring COVID-19 Impacts on Households in Uganda : Findings from the Seventh Round of the High-Frequency Phone Survey - World Bank (Washington, DC: World Bank, 2022)
In June 2020, the Uganda Bureau of Statistics, with the support from the World Bank, has launched the high-frequency phone survey on Coronavirus disease 2019 (COVID-19) to track the impacts of the pandemic on a monthly basis for a period of 12 months. The survey aimed to recontact the entire sample of households that had been interviewed during the Uganda national panel survey 2019-20 round and that had phone numbers for at least one household member or a reference individual. This report presents the findings from the seventh round of the survey that was conducted between October 15th and November 15th, 2021.